Função pulmonar na idade pré-escolar de recém-nascidos pré-termos com displasia broncopulmonar - Pirtouscheg, Carolina (2015)
Introduction: Premature birth can cause adverse effects on the growth and development of the lungs, changing lung function and impairing respiratory health throughout life, especially in infants who develop bronchopulmonary dysplasia (BPD). The objective of this study was to evaluate lung function in preschool children classified at birth as preterm newborns (PTNB) of very low weight and with and without diagnosis of BPD. Methods: An evaluation of lung function was performed, by means of spirometry, in 57 preschool aged children (3-6 years) with less than 34 weeks gestational age and weight less than 1500g at birth. The children were divided into two groups, with and without a history of BPD. The Student t or Mann-Whitney tests were used according to the normality of the data and the Fisher test. Multiple linear regression analysis was performed to evaluate the effect of the characteristics of the children in the neonatal and preschool age period as regards lung function. The significance level of 5% was adopted. Results: There were no statistically significant differences in the parameters evaluated in spirometry in children with and without BPD. The success rate in accomplishing spirometry was high (96.61%). 33.33% of the children evaluated showed alterations in at least one parameter in the pulmonary function test, with the FEV0,5 being altered the most frequently (84.2%). The variance analysis showed lower FEV0,75 scores in those children who used mechanical ventilation (p = 0.049), regardless of its duration. Conclusion: There is impairment in lung function in preschool age in preterm newborns (PTNB) with no differences between the groups with and without BPD.